A Review of The Effectiveness of Recruitment Approaches: Enhancing Employee Quality and Organizational Competitiveness - Musaba, Musaba; Mawardi, Ahmad; Ihsan, Saiful; Laksono, Agung; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to analyze and assess the effectiveness of recruitment strategies in attracting and selecting qualified candidates. Issues discussed include a variety of factors that influence the success of recruitment strategies, including the use of online platforms, company branding, and compliance with organizational culture. The proposed solutions include increased platform utilization, corporate branding development, HR training, and partnerships with other institutions. The data/objects used in this study include documents and policies related to the employee selection model. The method used is a qualitative approach by combining literature reviews, case studies, and interviews with relevant stakeholders. The results show that a directed, integrated and innovative recruitment strategy has an important role in creating quality employees and competitiveness, as well as ensuring efficient use of budgets. The discussion concluded that the human resources function needs to develop policies, involve stakeholders, and utilize information technology optimally to achieve better strategic goals in the selection of new employees.